The Rural–Urban Difference in Interpersonal Regret. (April 2016) - Komiya, Asuka; Oishi, Shigehiro; Lee, Minha
The present research examined rural–urban differences in interpersonal regret. In Study 1, participants who grew up in rural areas reported stronger interpersonal regret than those who grew up in large cities. In Study 2, we conducted an experiment and found that participants who were assigned to imagine a rural life reported greater interpersonal regret than those who were assigned to imagine an urban life. Moreover, this rural–urban difference was mediated by the degree to which participants wrote about informal social control such as gossip and reputation concerns. Finally, in Study 3, we used the pictorial eye manipulation, which evokes a concern for informal social control, and found that participants from large cities who were exposed to the eyes reported more intense interpersonal regret than those who were not exposed to the eyes. Together, these studies demonstrate that informal social control is a key to understanding rural–urban differences in interpersonal regret.